Plastic deformation of polycrystalline molybdenum: Experimental data and macroscopic model accounting for its anisotropy and tension–compression asymmetry. (1st December 2015) - Kleiser, Geremy J.; Revil-Baudard, Benoit; Cazacu, Oana; Pasiliao, Crystal L.
Abstract: In this paper a systematic experimental investigation of the room-temperature mechanical response of polycrystalline commercially pure molybdenum (Mo) is presented. It was established that the material has ductility in tension at 10 −5 /s and that the failure strain is strongly dependent on the orientation. A specimen taken along the rolling direction sustains large axial strains (20%), while a specimen taken at an angle of 45° to the rolling direction could only sustain 5% strain. It was observed that irrespective of the loading orientation the yield stress in uniaxial compression is larger than in uniaxial tension. While in tension the material has a strong anisotropy in Lankford coefficients, in uniaxial compression it displays weak strain-anisotropy. An elastic-plastic orthotropic model that accounts for all the specificities of the plastic deformation of the material was developed. Validation of the model was done through comparison with data on notched specimens. Quantitative agreement with both global and local strain fields was obtained. In particular, the effect of loading orientation on the response was very well described.